2015
DOI: 10.1017/s1431927614014482
|View full text |Cite
|
Sign up to set email alerts
|

Compositional characterization of iron gall inks in manuscripts

Abstract: When dealing with historical artifacts, non-destructive analytical methods for characterization are imperative. Proton Induced X-ray Emission (PIXE), when using an external micro beam, is considered to be an efficient technique for studying historical documents [1]. Besides the high sensitivity of this technique, the small dimension of the beam jointly with the raster capabilities of the setup [2] allows the examination of specific parts of the document and also the study of the ink composition and distributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Doncea and Ion (2014) identified the characteristic bands of cellulose in the historical paper at 1000 and 1400 cm −1 . The characteristic absorption bands of cellulose at 3450, 1200, 1150–980 cm −1 (Viegas, 2014). Additionally, the characteristic bands of calcite as inorganic filler C-O asymmetric stretching mode had been noticed in the FTIR spectra of historical paper sample at 1417.73 cm −1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Doncea and Ion (2014) identified the characteristic bands of cellulose in the historical paper at 1000 and 1400 cm −1 . The characteristic absorption bands of cellulose at 3450, 1200, 1150–980 cm −1 (Viegas, 2014). Additionally, the characteristic bands of calcite as inorganic filler C-O asymmetric stretching mode had been noticed in the FTIR spectra of historical paper sample at 1417.73 cm −1 .…”
Section: Resultsmentioning
confidence: 99%
“…Zoleo et al (2014) identified the characteristic peak of carbonate at 1402 cm −1 in illuminated paper manuscript dated back to 15th century. Viegas (2014) reported the characteristic absorption bands of calcite at 1414, 1085 and 874 cm −1 .…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, exposure to the room environment influences the chemical composition of this component, which can also influence the behavior of the PETSCA/Fe composite. Some oxidation reactions result in acid generation, while others result in the dissolution and mobilization of iron and other heavy metals present in the environment [6]. The direct mechanism of conversion in melanterite crystals in the PETSCA/Fe composite was probably similar to the initial stages of the oxidation of pyrite, as shown in Eq.…”
Section: Characterization Of the Samplementioning
confidence: 90%
“…Furthermore, the reduced penetration of the ink into the paper (less than 1 µm) makes it difficult to separate the signals from the paper and the ink by means of the characterization techniques used in this study. By Rutherford backscattering spectrometry, using a 2 MeV alpha particle beam and vacuum conditions, it was possible to obtain the depth penetration of these inks always being lower than 550 nm [32]. Nevertheless, it should be pointed out that under those experimental conditions, the beam induces non-reversible damage on the samples.…”
Section: Discussionmentioning
confidence: 99%